Technological Change and Market Structure: An Empirical Study - Mansfield, Edwin (American Economic Review, 1983)
It has long been recognized that technological change is one of the major forces influencing an industry's market structure. Karl Marx stressed this fact over a century ago. Like Marx, many economists, including Arthur Burns (1936) and John Kenneth Galbraith (1967), have been convinced that technological change tends to increase plant sizes and the level of industrial concentration. Others, like John Blair (1972), have argued that, although such a trend existed in the past, it has been reversed since World War II because of a fundamental change in the nature of technological advance whereby centralizing technologies have been displaced and superceded by decentralizing technologies. In recent years, there has been a revival of interest in the effects of technological change on market structure. Richard Nelson and Sidney Winter (1978) have formulated a computer model and Richard Levin (1980) has estimated an econometric model, both aimed at representing these effects. In general, these models seem to suggest that a relatively rapid rate of technological change in a particular industry is likely to result in a relatively high level of concentration. However, these authors are careful to point out that their results are preliminary and tentative. Although the effects of technological change on market structure are of fundamental importance to both economic analysis and public policy, it is surprising how little systematic study has been devoted to them. We know little or nothing about the effects of the various process and product innovations that have occurred in recent years in various industries. And we have very little information concerning the relationship between the rate of technological change in a particular industry and the changes in the industry's market structure. My purpose in this paper is to try to begin filling these notable gaps.